Analysis of Cash Turnover to Improve Company Profitability at PT Hutama Karya - Amy Badriyah Siregar; Nazwa Hadiarani; Suci Agsani; Henny Andriyani Wirananda; Sri Wardany (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze cash turnover including cash flows from operating, investing, and financing activities and their impact on increasing profit at PT Hutama Karya (Persero). The data used in this study were derived from the consolidated financial reports of PT Hutama Karya, published by the Indonesia Stock Exchange (IDX) for the period 2020–2024. The results indicate that although operating and investing cash flows consistently recorded deficits, the company was able to maintain liquidity through external financing. Effective cash management and a structured accounting information system have proven to support financial decision-making processes that positively impact profitability, especially since 2023. Thus, the cash receipt and disbursement system serves not only as an administrative tool but also as a strategic instrument in the company’s long-term financial planning.